A English - Famila Dwi Winati; Fauzan Romadlon (Fakultas Seni Rupa dan Desain ITB, 2021)
Bus Rapid Transit (BRT) is one of the alternative public transportations in urban areas, which has begun to be implemented in some cities of Indonesia. By finding out the effectiveness of BRT as a mass transportation system, it is necessary to study the expectations of users and non-users of the Trans Jateng Purwokerto-Purbalingga BRT regarding the perceived social, economic, and environmental impacts. This study uses the text Clustering method to group public opinion based on similarities so that it can be analyzed further for policymaking. As a result, the majority of the community gave positive expectations of BRT implementation’s perceived social, economic, and environmental benefits. On the other hand, public opinion on the presence of BRT is not always positive and has a significant impact. Improvements are needed in several aspects that are considered not to meet public expectations to maximize the function of BRT as a substitute for public transportation for private vehicles.